Understanding Chinese International Students’ Stances on Anti-China Rhetoric: A Postcolonial Perspective - Yin, Peng (Journal of college student development, 2023)
Along similar lines, Bhabha (1990, 1994) questioned the tenability of colonial authorities, introducing the notions of hybridity and the third space, which stressed the potential of (post)colonial subjects to resist the coloniality of power and imagine alternative ways of being and becoming. DATA The study reported here came from a larger project developed to design and validate a survey instrument to measure Chinese international students’ attitudes toward anti-China rhetoric. METHODS AND FINDINGS Data analysis occurred in a recursive manner, featuring an iterative process of coding and analytic memoing grounded in the tradition of qualitative thematic analysis (Boyatzis, 1998). To alleviate the undue influence of the researcher’s subjectivity, I kept a self-reflective journal (Morrow, 2005) throughout the process of data analysis. When the demographic information of the students was taken into consideration, the patterns of student responses suggested that the students at the upper level (junior and senior years) tended to be more inclined to take a critical stance on anti-China rhetoric than their counterparts at the lower level. Besides the endorsing and critical stances, other Chinese international students tended to adopt a dubious stance on anti-China rhetoric.